The Use of ChatGPT in Enhancing Students Writing Ability - Anggeraja, Moh. Fikri Amir; Samtidar, Samtidar; Aeni, Nur (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research aims to find out students' perceptions of difficulties, advantages and disadvantages in using ChatGPT and how ChatGPT enhance students' English writing ability. The subject of this research was five English students of Universitas Negeri Makassar. The interview was used as the main instrument to collect the data. The results of this research showed that all five subjects experienced an improvement in their writing ability, especially in terms of improving vocabulary, structure, grammar, explaining ideas well, reviewing and correcting, where this was due to ChatGPT helping them in a way that when the subjects asked something, ChatGPT would immediately provide explanations and examples. However, the level of improvement varies depending on how often and consistently it is used. This research contributes to the understanding of how ChatGPT improves writing skills. Essentially, the findings focus on students' perceptions of using ChatGPT as a writing aid. Although the results of this study emphasize more on students' understanding and subjective views, teachers can consider the application of ChatGPT to support the learning process.